Assessment of mangrove rehabilitation success at PT Kandelia Alam, Kubu Raya Regency, Indonesia - Jayanti, Ucy; Helena, Shifa; Sofiana, Mega Sari Juane; Ihsan, Nur Ramadhani (Journal of Marine Resources and Coastal Management, 2026)
Mangrove forests provide essential ecological and economic services; however, increasing human activities and natural disturbances have led to widespread degradation, highlighting the need for effective rehabilitation efforts. This study evaluated the success of mangrove rehabilitation in the concession area of PT Kandelia Alam, Kubu Raya Regency, Indonesia, using indicators of survival rate, plant height, leaf number, and environmental conditions. Data were collected under three site conditions (flooded, flowing-water, and unflooded areas) across two observation stations, each consisting of three measurement plots. Each plot measured 20 × 50 m and contained a 20 × 20 m subplot representing 100 individual plants, with observations conducted up to T₀ + 9. The results indicated that rehabilitation success at Stations I and II was moderate, with survival rates of 74.33% and 72.17%, respectively. Average plant heights were 50.60 cm at Station I and 53.66 cm at Station II, with an average of five leaves per individual at both stations. The Rhizophora  mucronata and Bruguiera gymnorrhiza species exhibited better adaptability in flowing-water and unflooded areas, whereas the Rhizophora apiculata species showed lower survival rates, particularly under flooded conditions. Environmental parameters at both stations were generally within suitable ranges for mangrove growth, including salinity of approximately 22 ppt, water temperature of 28°C, water pH of 7, soil temperature of 30–31°C, soil pH of 5.5, and substrates dominated by silty clay and silt. These findings suggest that while survival rates indicate moderate rehabilitation success, vegetative growth remains suboptimal, emphasizing the importance of site–species matching, hydrological suitability, and early-stage maintenance to enhance long-term mangrove rehabilitation outcomes.